Star Wars : The Force awakens Episode VII - Abrams, J. J. 1966-; Kennedy, Kathleen, 1954-; Burk, Bryan, 1968-; Kasdan, Lawrence, 1949-; Arndt, Michael D.; Ford, Harrison, 1942-; Hamill, Mark; Fisher, Carrie; Driver, Adam; Ridley, Daisy, 1992-; Boyega, John; Isaac, Oscar; et al. (Burbank, CA Lucas Film Ltd, 2016)
As Kylo Ren and the sinister First Order rise from the ashes of the Empire, Luke Skywalker is missing when the galaxy needs him most. It's up to Rey, a desert scavenger, and Finn, a defecting stormtrooper, to join forces with Han Solo and Chewbacca in a desperate search for the one hope of restoring peace to the galaxy.
Based on characters created by George Lucas.
Originally released as a motion picture in 2015.
Widescreen (2.40:1).
Harrison Ford, Mark Hamill, Carrie Fisher, Adam Driver, Daisy Ridley, John Boyega, Oscar Isaac, Lupita Nyong'o, Andy Serkis, Domhnall Gleeson, Anthony Daniels, Peter Mayhew, Max Von Sydow, Harriet Walter, Judah Friedlander.
DVD, NTSC, region 1, widescreen (2.40:1) presentation; 5.1 Dolby Digital, 2.0 Dolby Digital.
106626
Keywords: Skywalker, Luke; Organa, Leia; Solo, Han; Robots; Life on other planets; Space warfare; Good and evil; Fiction films; Science fiction films; Action and adventure films; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films -- United States; Feature films -- Great Britain; Drama